Manuscrits orientaux à Sarajevo - Lejla Gazić; Ramiza Smajić (Revue des Mondes Musulmans et de la Méditerranée)
Arabic, Turkish and Persian literature is well represented in Bosnia-Herzegovina where the memory of its days as part of the Ottoman Empire is still alive. The Gazi Husrev Bey library, the oldest one in Sarajevo, preserves an important collection of manuscripts which had been spared in the 1992-1995 War; the publication of its catalogue was taken up again in 1998. On the other hand, the Oriental Institute and its 5,263 manuscripts, its archives which held more than 300,000 documents in addition to the inventories and documents left behind by researchers was totally destroyed in May 1992. Other smaller collections exist which are currently being catalogued. The National University Library were also destroyed in 1992 but the manuscript collection, of which 400 concern the Middle Eastern field, were saved. Nonetheless, the conditions in which they are being preserved are not good and they are not out of danger.